Analysis and in situ mapping of the Adh locus in species of the willistoni group of Drosophila. - Rohde, C.; Abdelhay, E.; Pinto, H.; Schrank, A.; Valente, V.L.S. (Cytobios, 1995)
The Adh locus was mapped by in situ hybridization with the heterologous biotinylated probe SAC-PAT to the salivary chromosomes of seven species of the willistoni group of Drosophila. Hybridization signals were obtained mainly at a single site to the right arm of chromosome II in six species, but in Drosophila nebulosa two sites hybridized with the same consistency. Southern blot analysis Eco RI-digested genomic DNA of the seven species revealed high molecular weight bands shared by three species, plus the appropriately sized fragment expected, suggesting the presence of Adh pseudogenes in those species.